Characterization of gelatin film supplemented with carboxymethyl cellulose from pineapple core - Jirukkakul, Natcharee; Hemung, Bung-orn; Suebsuntorn, Jaruvan (Asia-Pacific Journal of Science and Technology, 2025)
Pineapple (Ananus comosus) cores, waste from pineapple processing, contain cellulose and exhibiting a potential for food packaging. The edible film made from gelatin and carboxymethyl cellulose (CMC) synthesized from cellulose extracted from pineapple core showed a light-yellow color and smooth surface. They had the same moisture content, morphology and tensile strength as film from gelatin with commercial CMC. The solubility, thickness, water vapor permeability, and antioxidant activity were also similar. Thus, CMC from pineapple core has the potential for edible film applications which was evaluated compared to commercial CMC.